Seasonal abundance and suppression of fruit-piercing moth Eudocima phalonia (L.) in a citrus orchard in Sarawak. - Chan, Stephen Teck Leong; Kueh, Roland Jui Heng (Hindawi Publishing Corporation, 2011)
Seasonal population of the fruit-piercing moths Eudocima spp. was monitored throughout the citrus growing seasons in a citrus orchard and in site adjacent to secondary forest from July 2007 to June 2009. The moth was detected practically throughout the year with activity lowest during the wet months (September-February) when fruits are still available and while highest during the dry months (May-June) which also coincided with the main fruiting season. The effects of an nC24 horticultural mineral oil (HMO) on the citrus fruit damage caused by fruit-piecing moths was also determined. The percent fruit damage was significantly lowest (P 0.05) in HMO-treated plots (8.4), followed by Dimethoate-treated plots (11.6) and untreated plots (22.5). However, there was no significant difference between HMO and Dimethoate treated plots indicating HMO is effective in reducing percent fruit damage.